Correction to: International prospective observational cohort study of Zika in infants and pregnancy (ZIP study): study protocol - Jill F. Lebov; Juan F. Arias; Angel Balmaseda; William Britt; José F. Cordero; Luiz Augusto Galvão; Ana Lucía Garces; K. Michael Hambidge; Eva Harris; Albert Ko; Nancy Krebs; Ernesto T. A. Marques; et al. (BMC, 2019)
Following publication of the original article [1], the author mentioned that two additional NIH staff were involved in the development of the protocol who did not receive recognition in the Acknowledgments section in their published article.